A novel HLA‐C allele, HLA‐C*06:45, identified by sequence‐based typing in a Chinese individual. Issue 1 (18th April 2013) - Wang, J.; Xia, L.; Luo, M.; Chen, Q.
<x xml:space="preserve">Abstract</x> HLA‐C*06:45 differs from HLA‐C*06:02 by a single G to A substitution at position187.